3D-printed OAM beam generator with an enhanced out-of-band gain filtering characteristic - Li, Jianxing; Wu, Sifan; Li, Zeting; Cao, Yuanxi; Xu, Kai-Da (Optics express, 2024)
In this paper, a 3D-printed orbital angular momentum (OAM) beam generator is proposed with integrated gain-filtering characteristics. The proposed design is composed of an integrated all-resonator 1-to-8 filtering power divider, eight-phase delay lines with twisted waveguides, and an eight-horn circular array. Unlike conventional fabrication methods, the proposed OAM generator is monolithically fabricated using selective laser melting (SLM) 3D-printing technology. Experimental results demonstrate that the proposed design achieves OAM beams with mode number l =+1 and a mode purity of around 80%. Additionally, it exhibits a gain-filtering response with out-of-band suppression levels exceeding 30 dB in the main beam directions. The air-filled all-metal structure allows the OAM beam generator to achieve a maximum total efficiency of over 80%. The proposed OAM generator with gain filtering response not only enhances channel capacity but also helps to avoid adjacent frequency interference, demonstrating great potential in millimeter-wave (mm-Wave) wireless systems.